Swelling Mechanisms of UO2 Lattices with Defect Ingrowths - Gunay, Seckin D. (PUBLIC LIBRARY SCIENCE, 2015)
The swelling that occurs in uranium dioxide as a result of radiation-induced defect ingrowth is not fully understood. Experimental and theoretical groups have attempted to explain this phenomenon with various complex theories. In this study, experimental lattice expansion and lattice super saturation were accurately reproduced using a molecular dynamics simulation method. Based on their resemblance to experimental data, the simulation results presented here show that fission induces only oxygen Frenkel pairs while alpha particle irradiation results in both oxygen and uranium Frenkel pair defects. Moreover, in this work, defects are divided into two sub-groups, obstruction type defects and distortion type defects. It is shown that obstruction type Frenkel pairs are responsible for both fission-and alpha-particle-induced lattice swelling. Relative lattice expansion was found to vary linearly with the number of obstruction type uranium Frenkel defects. Additionally, at high concentrations, some of the obstruction type uranium Frenkel pairs formed diatomic and triatomic structures with oxygen ions in their octahedral cages, increasing the slope of the linear dependence.
Keywords: MOLECULAR-DYNAMICS SIMULATION; INTERATOMIC POTENTIALS; THERMAL-PROPERTIES; URANIUM-DIOXIDE; RECOVERY; Science & Technology - Other Topics